Pengaruh Aromaterapi Jasmine Essential Oil Terhadap Skala Nyeri Pada Pasien Post Sectio Caesarea Di Ruang Anyelir Rumah Sakit Mitra Siaga Tegal - Nadia Riski Anisa; Ita Nur Itsna; Tri Susriyati (Institut Nalanda, 2024)
Sectio caesarea is a surgical procedure in which the fetus is born through incisions in the abdominal wall and uterus of the mother, this operation can be done urgently or scheduled. The impact that can cause sectio caesarea is pain. Pain is an unpleasant emotional and sensory experience but it can be alleviated with aromatherapy jasmine essential oil. This study physical examination, documentation and research instruments. Those were presented in the form of narrative text. The pain scale before jasmine essential oil aromatherapy was 6 in respondent 1, the pain scale was 4 in respondent 2. After being given jasmine essential oil aromatherapy for 3 days, there was a decrease in the pain scale to 3 in respondent animed to determine the effect of giving jasmine essential oil aromatherapy to reduce pain scale in post sectio caesarea patients.This study was descriptive research with a case study approach. The subjects of the study were postoperative patients sectio caesarea.Data were obtained through interviews, observation and 1 and the pain scale to 2 in respondent 2. It can be concluded that there was a decreasing effect of pain scale after giving jasmine essential oil aromatherapy. Health workers are expected to carry out non- pharmacological therapies and provide nursing care by providing jasmine essential oil aromatherapy to reduce pain scale in post sectio caesarea